THE ROLE OF DIGITAL TECHNOLOGIES IN ENHANCING THE COMPETITIVENESS OF INDUSTRIAL ENTERPRISES - Quldasheva Nargiza Komoliddin qizi; Olimjonova Nilufar Abdulaziz qizi (Modern American Journals, 2025)
This thesis examines the main characteristics of industrial enterprises in the digital economy, sheds light on the multifaceted nature of digitization in industrial operations and its consequences.
Keywords: Digital economy, industrial enterprises, digital technologies, artificial intelligence, cloud computing.